E-Commerce Adoption Among Small and Medium Enterprises in Saudi Arabia - Almoawi, Abdul Rahman Nasser A. (2011)
The purpose of this study was to determine the relationships between contexts and the e-commerce adoption among SMEs in Saudi Arabia. These contexts included organisational (firm size, attitude, innovativeness, knowledge), technology (relative advantage, compatibility, complexity), and environmental characteristics (competition intensity, information intensity). The study also attempted to determine the moderating effect of culture on these relationshps. Rogers's (2003) Diffusion of Innovations Theory and Tomatzky and Fleischer's (1990) method were used as a basis for the framework. In addition, Hofstede's cultural dimensions (power distance, uncertainty avoidance, individualism, and masculinity) were used as moderators. A quantitative and survey research design was adopted to collect data, test hypotheses, and answer research questions in the study. A total of 1150 questionnaires were sent to SME owner/managers in Saudi Arabia, and 400 were returned, giving a response rate of 34.78 percent. The results of the study revealed that attitude, firm size, competition intensity, and information intensity had a significant, positive relationship with the e-commerce adoption. However, knowledge and relative advantage had a significant negative relationship with the e-commerce adoption. In addition, the results showed that power distance, uncertainty avoidance, individualism, and masculinity had partially moderating effect on the relationship between organisational context and e-commerce adoption and the relationship between environmental context and e-commerce adoption. Regarding technology context, the result showed that power distance and masculinity had partially moderating effect on e-commerce adoption. On the contrary, the results found that uncertainty avoidance and individualism had no moderated effects. This research adds to the existing body of knowledge on e-commerce adoption and discovers additional contexts by offering organisational, technology, and environmental characteristics and the moderating effect of culture on the influence of these contexts regarding the adoption of e-commerce technology among SMEs for more informed decisions. The OTE Model of Innovation Adoption, the DoI theory, and Hofstede's cultural dimensions combined to form a richer theoretical framework that guided the understanding and prediction of e-commerce adoption among SMEs. In addition, this study showed SME owner/managers the opportunities and benefits of e-commerce adoption in a business environment. Furthermore, the results of the study may provide solutions and recommendations for SMEs and governments to successfully implement ecommerce.